THE IMPACT OF TECHNOLOGY ON STRENGTHENING BASIC HUMAN RIGHTS: REASSESSING PROPERTY RIGHTS ENFORCEMENT IN ALBANIA - Ziu , Kejsi (International Journal of Legal and Social Order, 2025)
Technology has emerged as a transformative force in reinforcing fundamental human rights, particularly the right to property as protected under Article 1 of Protocol No. 1 to the European Convention on Human Rights (ECHR). Albania’s persistent challenges in enforcing property rights—rooted in post-communist restitution complexities, weak enforcement mechanisms, and administrative opacity—have led to repeated condemnations by the European Court of Human Rights (ECtHR). This paper reassesses Albania’s property rights regime through a technological lens, exploring how digital innovation can enhance transparency, accountability, and access to justice. By analysing landmark ECtHR judgments and Albania’s legal framework, it argues that digitisation of property registries and e-justice mechanisms can address the systemic deficiencies that have hindered effective enforcement. The study concludes that technology, if strategically integrated within Albania’s justice and administrative systems, can serve as a catalyst for fulfilling ECHR obligations and advancing the rule of law as part of the European integration process.